As espacialidades homossexuais masculinas como constituidoras da urbanidade: análise histórico-comparativa entre São Paulo e Paris em 1995 e 2016 - Vinicius Santos Almeida (Confins)
This article seeks to understand the relation between urbanity and male homosexual spatialities in São Paulo and Paris, through a space-temporal comparison (1995 and 2016). We consider that this relation is dialectic and that as more urbanity a city has, the more these spatialities can express themselves publicly, in search of social recognition. By looking at this subject through maps that shows us the elementary structures of gay spatialities, we present at the end a synthesis model of the organization of the space to each city. To conclude, we make a discussion about spatial justice, with the aim to defend the need to overcome the debate about the gay ghetto.